Aboveground biomass and volume equations for Pinus halepensis Mill., in Coahuila, Mexico - Montoya Jiménez, Juan C.; Méndez González, Jorge; Sosa Díaz, Librado; Ruíz González, Cecilia G.; Zermeño González, Alejandro; Nájera Luna, Juan A.; Manzano Camarillo, Mario G.; Velázquez Rodríguez, Alma S. (Instituto de Ecología, A.C., 2018)
Conducting studies to measure biomass in terrestrial ecosystems is essential to assess carbon stores and how forest species contribute to the mitigation of climate change. The objective of this study was to adjust allometric equations to estimate aerial biomass and volume of Pinus halepensis Mill. in the Sierra de Zapalinamé, Coahuila. It was assumed that the variables basal diameter and height adequately predict aerial biomass and volume of P. halepensis. 40 trees were used, with basal diameter that varied from 25 cm to 75 cm. The biomass of stem and branches (64%) was, on average, double that of leaves and twigs (36%) and its proportion increased with respect to the total height of the tree, according to the equation: y = 53.4 + 1.2x. The best fits were in volume (R2 = 0.82) and total biomass (R2 = 0.77) with allometric equations of logarithmic linear form, with diameter and height as independent variables (lny = β0 + β1ln (Db2H). Aerial biomass of P. halepensis was 2.5 times smaller than that of other coniferous species, possibly due to the fact that the trees of this species branched almost from the base of the tree, on average 85% of the tree presented branches between 5 cm and 10 cm in diameter.